2017
DOI: 10.13057/nusbiosci/n090111
|View full text |Cite
|
Sign up to set email alerts
|

Blood cockle (Anadara granosa) supplementation to increase serum calcium level and femur growth of low-protein diet rat

Abstract: Abstract. Solang M. 2017. Blood cockle (Anadara granosa) supplementation to increase serum calcium level and femur growth of lowprotein diet rat. Nusantara Bioscience 9: 62-67. Blood cockle (Anadara granosa) contains protein, zinc and calcium. The aim of this study was to evaluate the effects of blood cockle flour supplement on serum calcium level, rat femur length and weight of rat femur on low-protein diet. The design of research used The Separate Sample Pre-Post Test Design. Forty eight Wistar male rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Albumin plays an important role in transporting calcium, which means that there is a relationship between calcium absorption and protein intake. Therefore, lowprotein diet causes lower calcium absorption; hence, the level of calcium in the blood decreases (Solang 2017). Moreover, induction Administration of MBD containing LAB did not significantly affect serum calcium level during pregnancy.…”
Section: Effects Of Milk-based Drink Containing Lactic Acid Bacteria On Serum Calciummentioning
confidence: 92%
See 1 more Smart Citation
“…Albumin plays an important role in transporting calcium, which means that there is a relationship between calcium absorption and protein intake. Therefore, lowprotein diet causes lower calcium absorption; hence, the level of calcium in the blood decreases (Solang 2017). Moreover, induction Administration of MBD containing LAB did not significantly affect serum calcium level during pregnancy.…”
Section: Effects Of Milk-based Drink Containing Lactic Acid Bacteria On Serum Calciummentioning
confidence: 92%
“…This might be due to the induction of undernutrition. Study by Solang (2017) showed that induction of undernutrition in rats by administering an 8.46% protein diet for eight weeks showed a decrease in serum calcium level by 31.4% compared to the control group given 13-15% protein for 8 weeks. Moreover, calcium level in the control group was 11.8±0.20 mg/dl (Solang 2017).…”
Section: Effects Of Milk-based Drink Containing Lactic Acid Bacteria On Serum Calciummentioning
confidence: 99%
“…Bahan pangan yang merupakan sumber protein alternatif dan zink diantaranya adalah kerang. Kerang darah asal Gorontalo menunjukkan mengandung protein total 27,26%, sedangkan kandungan mineral antara lain: zinc 81,16 ppm, Fe 1720,46 ppm, Cu 4,26 ppm, dan Ca 318,67 ppm (Solang et al, 2013;Solang, 2017). Kerang tersedia cukup melimpah di desa Iloheluma Kecamatan Patilanggio Kabupaten Pohuwato dan harganya terjangkau namun belum termanfaatkan secara maksimal., Pemanfaatan untuk konsumsi hanya dilakukan pada saat perayaan hari raya ketupat.…”
Section: Pendahuluan 1analisis Situasiunclassified